Evaluation of the predictive value of coronary artery calcium score for obstructive coronary artery disease in asymptomatic Korean patients with type 2 diabetes mellitus. Issue 2 (March 2015) - Won, Ki-Bum; Chang, Hyuk-Jae; Niinuma, Hiroyuki; Sung, Jimin; Shin, Sanghoon; Cho, In-Jeong; Shim, Chi-Young; Hong, Geu-Ru; Kim, Young Jin; Choi, Byung-Wook; Chung, Namsik
Abstract : Background: Compared with coronary computed tomographic angiography (CCTA), the coronary artery calcium score (CACS) may be limited in predicting adverse cardiovascular events in asymptomatic diabetic patients. Methods: We evaluated the predictive value of CACS for obstructive coronary plaques (OCPs) assessed by CCTA in 328 consecutive asymptomatic patients with type 2 diabetes mellitus who had an estimated glomerular filtration rate greater than 60 ml/min/1.73 m 2 . Results: In total, 29 (9%) patients had OCPs: calcified or mixed OCPs and noncalcified OCPs were found in 26 (8%) and three (1%) patients, respectively. On the basis of a CACS of 0, 1–10, 11–100, and greater than 100, OCPs were found in 2, 5, 15, and 36% of patients, respectively. On receiver operating characteristic curve analysis, the optimal cutoff CACS for predicting OCPs was found to be 33, with 83% sensitivity and 81% specificity (area under the curve, 0.853; 95% confidence interval, 0.777–0.930; P <0.001). Positive and negative predictive values of a CACS of 33 for OCPs were 30 and 98%, respectively. On multivariate logistic regression analysis, age [odds ratio (OR), 1.09], microalbuminuria (OR, 3.43), current smoking (OR, 3.93), and CACS greater than 33 (OR, 15.85) were found to be independently associated with an increased risk for OCPs ( P <0.05, respectively). The predictive significance of CACS greater than 33 for OCPs improved after considering the status of microalbuminuria and current smoking. Conclusion: These findings suggest that CACS is an effective gatekeeper for evaluating obstructive coronary artery disease using CCTA in asymptomatic Korean patients with type 2 diabetes mellitus who have near-normal kidney function.